A catalogue of resistance gene homologs and a chromosome‐scale reference sequence support resistance gene mapping in winter wheat. Issue 9 (30th May 2022) - Kale, Sandip M.; Schulthess, Albert W.; Padmarasu, Sudharsan; Boeven, Philipp H. G.; Schacht, Johannes; Himmelbach, Axel; Steuernagel, Burkhard; Wulff, Brande B. H.; Reif, Jochen C.; Stein, Nils; Mascher, Martin
Summary: A resistance gene atlas is an integral component of the breeder's arsenal in the fight against evolving pathogens. Thanks to high‐throughput sequencing, catalogues of resistance genes can be assembled even in crop species with large and polyploid genomes. Here, we report on capture sequencing and assembly of resistance gene homologs in a diversity panel of 907 winter wheat genotypes comprising ex situ genebank accessions and current elite cultivars. In addition, we use accurate long‐read sequencing and chromosome conformation capture sequencing to construct a chromosome‐scale genome sequence assembly of cv. Attraktion, an elite variety representative of European winter wheat. We illustrate the value of our resource for breeders and geneticists by (i) comparing the resistance gene complements in plant genetic resources and elite varieties and (ii) conducting genome‐wide associations scans (GWAS) for the fungal diseases yellow rust and leaf rust using reference‐based and reference‐free GWAS approaches. The gene content under GWAS peaks was scrutinized in the assembly of cv. Attraktion.